Some early Russian studies of subsurface storm-flow processes - Smakhtin, Vladimir U. (Wiley, 2002)
Subsurface flow is an important component of the catchment hydrological cycle. Various mechanisms of this process and their role in storm-flow generation attracted the attention of many researchers throughout the twentieth century. The results of most of these studies are well documented. However, similar studies conducted in the past by many Russian hydrologists have never been made available to the English speaking hydrological community. This paper attempts to fill this gap and briefly review some of these investigations, focusing on their main results. It starts with the review of the early experimental studies (after 1930s-1950s), which allow the main characteristics of subsurface storm flow to be established. This is followed by a review of the research conducted in 1960s, which resulted in some conceptualization of the subsurface flow mechanisms. The paper also draws some parallels between this, mostly unknown, subsurface flow research in Russia and the better-known contemporary studies of this process.